Knowledge, attitudes and practices in oral health among families with preschool children in an urban poor community in Metro Manila - Oliveros, Maritess S.
The World Health Organization (WHO) estimates that about 9.8 out of 10 Filipino children have dental caries. Through its program, "Health For All by the year 2000" (HFA 2000), targets all people to have a quality of life that will allow them to live productively, free from avoidable burden of disease. The goal of the study is to identify the present oral health situation of families living in an urban poor community. Specifically, it aims for the following: 1. To determine the knowledge, attitudes and practices of oral health of preschool children and their parents; 2. To assess the oral health status of both parents and preschoolers; To determine whether the knowledge, attitudes and practice in oral health is related to the oral health status of both parents correlate with the knowledge, attitudes and practices in oral health and the oral health status of the preschoolers. The study focused on families with 5-6 year-old children living in Payatas, Quezon City. The sample was randomly selected from the list of the Barangay Nutrition Scholar and the enrollment list of the selected day care centers. Data collection was through an interview schedule and intraoral examination of the participants. Data analysis used descriptive statistics and ANOVA, Spearman and Chi-square analyses. Of the total 66 parent participant in the study, results showed that 94% was able to provide acceptable and satisfactory knowledge on oral health with evidence that their mean knowledge levels are similar across educational level. Parental attitudes towards oral health included the dentist among recognized health care providers (39.4%), admitted presence of dental fear (71.2%),dental visits triggered by the presence of a problem (40.9%, belief in regular dental visits (25.8%), twice a year dental check-ups (89.4%), and that children's teeth should be cared for (97%), disregard for a painless tooth decay (45.4%) and seeking treatment when it's painful already (42.2%), preference of tooth extraction over dental filling (80.3%)and awareness that tooth infection could infection could be life threatening (81.8%). Practices in oral health are twice a day (43.9%) to three times a day (39.4%) tooth brushing, toothbrush costing a maximum of Php 30.00 and toothpaste not more than Php 10.00, switching to new toothbrushes usually after every two months, tools to avoid interdental debris include toothpick, matchstick, thread, salt, substitution for toothpaste (68.2%), tooth extraction being the main reason for dental visits (92.4%) and that admitted awareness of dental problem depends om pain (63.3%) which triggers a decision to see a dentist (74.2%), and their 5-6 year-old children not having experienced their 1st dental visit (75.8%). Of the total 66 preschooler participants in the study, results showed that 62% had acceptable and satisfactory knowledge in oral health. Oral health attitudes included admitted dental fear (50%), dental visits because of pain (30.3%), belief in twice a year dental check-ups (83.3%), that children's teeth should be cared for (98.5%), and in asymptomatic tooth decay treatment (54.5%), preference of tooth extraction over dental filling (59.1%), belief that tooth infection is not life threatening (66.7%). Oral health practices are once a day (27.2%), twice a day (16.7%) and thrice a day (9.1%) frequency of toothbrushing, toothbrushing without supervision, recognition of dirty, broken ugly, beaten toothbrush means switch to new one, tools to remove interdental debris include toothbrush, finger, toothpick, or simply ignore it, toothpaste choice is because of taste, salt substitutes for toothpaste if unavailable (89.4%), awareness of dental problem depends on pain (62.1%), and claims of having no dental experience yet (65.2%). Only one age group, the 35-44-year-olds, passed the set specific oral health goals of HFA 2000 while the rest failed. Both parents and preschoolers' knowledge is independent of their oral health status and their supposed encouraging attitudes and practices in oral health do not accurately reflect on actual circumstances. The only aspect of parents' attitudes proven to have a relationship concerned their preference between filling and extraction --- elementary-level parents and high school-level parents would rather remove the tooth/teeth concerned that save it through a dental restoration while college-level parents opted to save rather than remove tooth/teeth.Conclusions of the study are as follows: 1. On the matter of knowledge, attitudes and practices in oral health: (a) Parent's knowledge in oral health is sufficient and satisfactory. (b) Positive attitudes towards oral health include acknowledgement of the dentist as healthcare provider, adequate oral hygiene awareness, belief in twice a year dental check-ups, and no need to care for children's teeth. (c) Negative practices persist, such as dental visits dictated by pain and preference of interventional over over preventive/conservative dentistry, despite desirable attitudes and awareness that dental complications should be fatal. (d)Children lack sufficient and satisfactory knowledge in oral health. (e) Children's attitudes and practices in oral health reflect those of their parent with the most glaring difference being the inability to perceive tooth infections as life threatening. 2. 7 years after the WHO's due date, only 1 age group (35-44 years old) sparingly passed the set specific oral health goals of HFA 2000. Thus oral health status of both parents and preschoolers are in unsatisfactory conditions. 3. Knowledge, attitudes and practices in oral health do not necessarily dictate an oral health status. 4. The level of educational attainment of parents does not have an impact on the knowledge, attitudes and practices in oral health of their families.